The effectiveness of a program based on the use of Puppet Theater in answering some common children’s questions in early childhood - Al-Humaydani, Tahani Mater (Journal of Curriculum and Teaching Methodology, 2023)
The study aims to reveal the effectiveness of the program based on the use of Puppet Theater in answering some common children’s questions (scientific-religious-sexual) in early childhood, the researcher used the semi-experimental approach with two groups to suit the nature of the current research, where the sample is divided into two groups, one of which is the experimental group The other is the control group, The researcher prepared and used the following tools: the illustrated common questions scale (prepared by the researcher), and the program based on the use of puppet theater in answering some common children’s questions in early childhood (prepared by the researcher), and it was applied to a sample of (60) boys and girls from Early childhood children, average age (4-6) years, and the results of the current research revealed the effectiveness of the program based on the use of puppet theater in answering some common questions of children in early childhood, as appeared from the dimensional measurement of the experimental group compared to the control group In addition to the continuity of the positive effect for the experimental group, as it appeared in the follow-up measurement of the children of the research sample and the results of his hypotheses showed, The researcher recommended that attention should be given to designing programs and activities that present common children’s questions to help children know the answers to them.